Societies "Friends of Literature" and Socio-cultural Life of the Ural City in the Late XIX - Early XX Century (Филологический класс, 2013)
This paper reviews the history of public organizations of literature and art that existed in the cities of the Urals in the late nineteenth — early twentieth century. The author gives a typology of urban social organizations that contributed to reproduction, development and dissemination of literature among the townspeople, or along with other cultural and educational functions assumed exercise of mutual assistance for their members. The article reconstructs features of literary life and the diversity of organizational forms of activity of associations of literature and art.